ChemInform Abstract: Modular Approach to Reductive C(sp2)—H and C(sp3)—H Silylation of Carboxylic Acid Derivatives Through Single‐Pot, Sequential Transition Metal Catalysis. Issue 36 (September 2015) - Hua, Yuanda; Jung, Seongjeong; Roh, James; Jeon, Junha
Abstract Benzoic acid esters (I) and (V), heteroaromatic esters (VIII) and (X), acetophenones (XII), benzaldehydes (XVII) as well as tetralone (XV) form corresponding annelated Si‐dialkylated 1, 2‐oxasilol derivatives via respective dialkylsilylated alcohols, e.